The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/asia.201200131
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Bright Heteroleptic Bis(dipyrrinato)zinc(II) Complex

Abstract: Let your light shine: The first example of a heteroleptic bis(dipyrrinato)zinc(II) complex, 7a, was synthesized from two types of dipyrrins prepared by a new deboration protocol for BODIPYs. Complex 7a showed a higher fluorescence quantum yield (0.76 in toluene) than the corresponding homoleptic complexes 5a and 6. The superiority of 7a as a luminophore was more prominent in more polar CH2Cl2 (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 18 publications
3
116
0
Order By: Relevance
“…47 Interestingly, a recent study on related mesityl-substituted zinc dipyrrins (zDIP2 and zDIP4) has reported that the quantum yields of the homoleptic complexes are strongly dependent on solvent polarity, decreasing from 20–30% in toluene to ≤5% in dichloromethane. 44 The authors proposed that this decrease in polar solvents is due to thermal promotion from a locally excited state on a single dipyrrin ligand to a nonemissive, charge-separated state (i.e., D + –Zn–D – ); 44 however, no additional photophysical data was provided to support this hypothesis. Strong excitonic coupling between nonorthogonal ligands has also been suggested as another nonradiative deactivation pathway of zinc π-extended dipyrrin complexes.…”
Section: Introductionmentioning
confidence: 99%
“…47 Interestingly, a recent study on related mesityl-substituted zinc dipyrrins (zDIP2 and zDIP4) has reported that the quantum yields of the homoleptic complexes are strongly dependent on solvent polarity, decreasing from 20–30% in toluene to ≤5% in dichloromethane. 44 The authors proposed that this decrease in polar solvents is due to thermal promotion from a locally excited state on a single dipyrrin ligand to a nonemissive, charge-separated state (i.e., D + –Zn–D – ); 44 however, no additional photophysical data was provided to support this hypothesis. Strong excitonic coupling between nonorthogonal ligands has also been suggested as another nonradiative deactivation pathway of zinc π-extended dipyrrin complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, the structures and luminescent properties of the five complexes were disclosed and discussed, together with those of 1a 2 Zn and 1c 2 Zn synthesized previously. 8 The complexes' spectroscopic properties in solution are summarized in Table 1, and their absorption spectra are shown in Figure 1a. The regions of absorption maxima (488−511 nm), molar extinction coefficients (1.2 × 10 5 −1.6 × 10 5 M −1 cm −1 ), and emission wavelengths (510−558 nm) are typical of bis(dipyrrinato)zinc(II) complexes and are attributable to the 1 π−π* transition of the dipyrrin core.…”
mentioning
confidence: 99%
“…The regions of absorption maxima (488−511 nm), molar extinction coefficients (1.2 × 10 5 −1.6 × 10 5 M −1 cm −1 ), and emission wavelengths (510−558 nm) are typical of bis(dipyrrinato)zinc(II) complexes and are attributable to the 1 π−π* transition of the dipyrrin core. 8 For complexes 2a 2 Zn− 2c 2 Zn, there is an additional absorption band around 370 nm, attributable to the 1 π−π* transition of the anthracene subunit. The constant absorption and emission wavelengths suggest that the meso-aryl groups of the complexes have little effect on the ground and photoexcited electronic states of the dipyrrin subunit.…”
mentioning
confidence: 99%
“…The structural feature implies that interaction in the ground state between the two moieties is not outstanding. Other structural features were almost the same as those of other bis(dipyrrinato)zinc(II) complexes: 8 The zinc centers adopted tetrahedral coordination spheres (dihedral angles: 87.45 and 82.90°for 1 and 2), and the zincnitrogen bond lengths spanned from 1.9681.976 ¡ (average: 1.973 ¡) for 1, and 1.9651.968 ¡ (average: 1.967 ¡) for 2. Figure 3 shows normalized UV-vis spectra of triarylamineconjugated bis(dipyrrinato)zinc(II) complexes 1 and 2 in toluene.…”
Section: Single-crystal Xrd Analysismentioning
confidence: 56%